Regio- and Stereoselectivity in the 1,3-Dipolar Cycloaddition Reactions of Isoquinolinium Ylides with Cyclopenta[a]acenaphthylen-8-ones - Yavari, Issa; Ravaghi, Parisa; Safaei, Maryam; Kayanian, Jasmine (Synlett, 2020)
A convenient regio- and diastereoselective synthesis of functionalized 5a,5b-dihydro-5H,13H-naphtho[1′′,8′′:4′,5′,6′]pentaleno[1′:3,4]pyrrolo[2,1-a]isoquinolin-5-ones via 1,3-dipolar cycloaddition reaction of 8H-cyclopenta[a]acenaphthylen-8-ones with carbonyl-stabilized isoquinolinium N-ylides, is described. Based on DFT calculations at b3lyp/6-311+g(d,p) level of theory, a nonconcerted mechanism is proposed to explain the regioselectivity of this reaction. The structure of a typical product was confirmed by X-ray crystallographic analysis.
Keywords: regioselective synthesis; 1,3-dipolar cycloaddition; isoquinolinium ylide; cyclopentadienones; DFT calculations